MYCOMIX - Exploring the toxic effects of mixtures of mycotoxins in infant food and potential health impact – a case study - Alvito, Paula (2015)
Mycotoxins are natural contaminants produced by fungi and its common occurrence in food poses a threat to human health, mainly to vulnerable population groups as children. In this presentation, the different questions, teams, methodologies applied in the national project Mycomix concerning the health effects of combined mycotoxins present in foods consumed by Portuguese children will be presented as a case study to assess the health impact of multiple chemicals in foodstuffs. The MycoMix Project (2013-15) funded by the Portuguese Foundation for Science and Technology (FCT, PT), aims to study the occurrence of multiple mycotoxins and toxicity interactions in infant foods and cereals consumed by Portuguese children and try to answer several questions: 1) Are Portuguese children exposed daily to one or several mycotoxins through food? 2) Can this co-exposure affect children´s health? and 3) Are there interactions between mycotoxins? Within this project, Portuguese children (< 3 years old, n=103) food consumption data were obtained using a 3 days food diary in a pilot study performed at a Primary Health Care Unit. The main declared infant foods were purchased at Lisboa market along 2014-15 and analyzed by means of HPLC and LC-MS/MS analytical techniques for multiple mycotoxins co-occurrence. Toxicological studies including bioaccessibility and cyto and genotoxic interactions between mycotoxins detected were also performed using in vitro methodologies.